2018
DOI: 10.5194/wes-2017-61
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Different Gray Zone Treatments in WRF-LES Real Case Simulations

Abstract: Abstract. When conducting meso-micro scale coupled atmospheric simulations, it is crucial to ensure an adequate treatment of gray zone or terra incognita resolutions in which a large portion of the kinetic energy is naturally produced by the momentum balance equations in the model, while the remaining part still needs to be parameterized. In this work, we conduct three multiday, real case, full-physics atmospheric simulations that are fully coupled from the meso to the micro scale and in which the only differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The Advanced Research WRF (WRF-ARW) is a state-of-the-art open source mesoscale atmospheric model, developed by National Center for Atmospheric Research (NCAR) for both research and numerical weather prediction purposes (Powers et al, 2017). This model, which is probably the most popular meteorological (it also has a climatic version) model worldwide, has the capability to be used for a wide range of applications, such as real-time numerical weather prediction, data assimilation, parameterized-physics research, regional climate simulations, air quality modeling, atmosphere-ocean coupling, and idealized simulations (Blossey et al, 2013;Doubrawa et al, 2018;Jimenez et al, 2016;Lin et al, 2015;Moeng et al, 2007;Montornès et al, 2016;Wang et al, 2009;Yamaguchi & Feingold, 2012;Zhong et al, 2016). In addition, it can be ran at different domains and offers various options for parameterization of convective processes, turbulent transports, evolution of surface temperature and soil moisture, and soil-air interactions (Ruiz-Arias et al, 2013;Skamarock et al, 2008).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The Advanced Research WRF (WRF-ARW) is a state-of-the-art open source mesoscale atmospheric model, developed by National Center for Atmospheric Research (NCAR) for both research and numerical weather prediction purposes (Powers et al, 2017). This model, which is probably the most popular meteorological (it also has a climatic version) model worldwide, has the capability to be used for a wide range of applications, such as real-time numerical weather prediction, data assimilation, parameterized-physics research, regional climate simulations, air quality modeling, atmosphere-ocean coupling, and idealized simulations (Blossey et al, 2013;Doubrawa et al, 2018;Jimenez et al, 2016;Lin et al, 2015;Moeng et al, 2007;Montornès et al, 2016;Wang et al, 2009;Yamaguchi & Feingold, 2012;Zhong et al, 2016). In addition, it can be ran at different domains and offers various options for parameterization of convective processes, turbulent transports, evolution of surface temperature and soil moisture, and soil-air interactions (Ruiz-Arias et al, 2013;Skamarock et al, 2008).…”
Section: Model Descriptionmentioning
confidence: 99%
“…They found that vertical motions and convective rolls are intensified in the subkilometer simulations with the scale-aware PBL parameterization. Since then, several studies have further investigated the effects of the SH parameterization and found that it performs better at gray-zone resolutions than its conventional parameterization of Hong et al (2006), which scheme has been developed at Yonsei University and thus is named YSU hereinafter (e.g., Doubrawa et al 2018;Xu et al 2018). However, all of these studies consider dry CBLs; the scale-aware PBL parameterization has not been tested for moist CBLs, where PBL parameterizations interact strongly with microphysical processes within convection.…”
Section: Introductionmentioning
confidence: 99%
“…The further 1 h outputs with 5 s interval (approximately the advection timescale of the smallest resolved eddies, which is equivalently twice the grid resolution of 20 m) were used for the analysis. We take advantage of the homogeneous turbulence in the spanwise direction (Ghannam et al, 2015) and calculate all resolved-scale turbulent quantities by averaging in the spanwise direction (the y direction) and in time t over the last 1 h period. This averaging is referred to as "the y − t averaging" hereafter and is denoted by ϕ , for example, for the y − t-averaged ϕ.…”
Section: Model Coupling and Configurationmentioning
confidence: 99%